The financial labor supply accelerator - Jeffrey R. Campbell; Zvi Hercowitz (Federal Reserve Bank of Chicago, 2011)
The financial labor supply accelerator links hours worked to minimum down payments for durable good purchases. When these constrain a household's debt, a persistent wage increase generates a liquidity shortage. This limits the income effect, so hours worked grow. The mechanism generates a positive comovement of labor supply and household debt, the strength of which depends positively on the minimum downpayment rate. Its potential macroeconomic importance comes from these labor supply fluctuations' procyclicality. This paper examines the comovement of hours worked and debt at the household level with PSID data - before and after the financial deregulation of the early 1980s which reduced effective down payments - and compares the evidence with results from model-generated data. The household-level data displays positive comovement between hours worked and debt, which weakens after the financial reforms. An empirically realistic reduction of the model's required down payments generates a quantitatively similar weakening.
Keywords: E24; 330; Borrowing Constraints; Durable Goods; Wage Shocks; Hours Worked